DAMPAK PENGGUNAAN TEKNOLOGI PERKANTORAN DALAM MENUNJANG TUGAS–TUGAS SEKRETARIS PIMPINAN DI POLITEKNIK NEGERI SRIWIJAYA - Ummasyroh Ummasyroh; Yusnizal Firdaus; Maria Selviana (Politeknik Negeri Sriwijaya, 2015)
This reseach is undertaken to identify The Impact of Office Technology (office machines) Usage In Supporting Tasks of Executive Secretary in Polytechnic of Sriwijaya”.To obtain the data and information from the institution, the authors use several methods of data collection, they are: observation, interviews, and documentation. The authors using qualitative method to analyzing the data in this article. The results show that the secretary has been using the office technology to supporting her office tasks. The use of office technology give a positive impact on employment, work procedures and outcome. While the negative impact that creates a feeling of dependency on office machines and causes larger costs for the institution.